A CRITICAL UNDERSTANDING OF MYASTHENIA GRAVIS AND IT'S TREATMENT IN AYURVEDA - A CASE STUDY - Panchal, *Vidyasagar; A.S, Prashanth (International Journal of Ayurveda and Pharma Research, 2018)
Relatively Myasthenia gravis is an uncommon disorder with an annual incidence of 10-20 new cases per million. Diagnosis follows a bimodal distribution with a predominantly female peak in the second and third decade of life and a predominantly male peak in the fourth to eighth decades. It presents with fluctuating skeletal muscle weakness and fatigue most commonly affecting the ocular muscles, although any muscle may be affected. MG affects 50 to 200 per million people. It is newly diagnosed in three to 30 per million people each year. Diagnosis is becoming more common due to increased awareness. Although there is still no cure for myasthenia gravis in modern sciences other than symptomatic management, Ayurvedic therapies can give much more promising results. Comparison between myasthenia gravis and diseases explained in Ayurveda is difficult and exact correlation is not possible. But based on Nidana, Roopa, Upashaya, and Anupashaya, a probable diagnosis can be made and treated accordingly. When aggravated, a single Dosha may cause manifold diseases depending upon the various etiological factors and the sites of manifestations. Hence nomenclature of all types of diseases in definite terms is not always possible. If a physician is not able to name a particular disease, he should not feel ashamed on that account. In the present study, Vatavyadhi chikitsa, Asthimajjagata vata chikitsa, Arditavat chikitsa and Avarana concepts were applied for diagnosis and treatment. Nasya, Nasapana, Basti chikitsa were planned accordingly. Vatakaphahara, Dhatvagni vardhana, Brimhana and Snehana dravyas were used in the management.